Evaluasi dan Pemodelan Proses Bisnis Menggunakan Business Process Management Notation dan Quality Evaluation Framework (QEF) Pada Perusahaan Gumcode Indonesia - Zulfiar Ryanda Putra; Aditya Rachmadi; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Gumcode Indonesia is a company engaged in the field of it development & outsourcing service with some cooperation with partners, agencies and state-owned enterprises (BUMN). Gumcode has several services in example website and both android and ios mobile apps that can be developed. In addition, Gumcode Indonesia also provides developer outsourcing service for the company. The business processes on Gumcode is certainly not running properly and correctly. There are still some problems that have potential to disrupt the business processes. As has been said by the speakers on Gumcode in February 2018, one of the problems that exist in the gumcode business process is the process runs too long. It require analysis and modeling of business processes in order to evaluate the existing business processes on CV. Gumcode Indonesia. This research uses value shop analysis to find out the main activity and supporting activity in business development process at the company, Quality Evaluation Framework (QEF) to evaluate business development process which have been analyzed and modeled. After that, root cause analysis acts to identify the root of problem using 5 Whys method analysis. The result of this research is in the form of cause and root of problem that happened at activity which have been evaluated. There is a discrepancy in the quality factor with the Q3 code that is the suitability of the offer to the client (Failure Frequency). Based on the results of interviews, the target of offering success on the average client is 10 offerings per week. And in per week on average only 3 offerings that made it into the company. Based on the calculation of Quality Factor obtained 30% results from 10 offers. Then the result of Quality Factor is in accordance with the target company